Assessment of knowledge, attitude, and practices on food safety and compliance to microbiological safety guidelines among vendors of commonly patronized street foods in Poblacion, Batangas City, Philippines - Argente, Myla A. (Journal of Human Ecology, 2020)
This cross-sectional study explored the association between the microbial safety of street foods, using E. coli load as indicator, and vendors’ knowledge, attitude, and practices on food safety and the environmental conditions of vending stalls in Poblacion, Batangas City in Batangas, Philippines. Thirty-five (35) street food vendors selling three commonly patronized street foods, namely, grilled pork intestine (isaw), pork barbecue, and grilled coagulated chicken blood (betamax), served as study respondents. Results showed that most street food vending sites were located in areas with no running water supply and handwashing facilities. Moreover, although trash bins were available, waste segregation was not practiced. Vendors had an average level of food safety knowledge and good attitude towards food safety, although these did not translate into practice. Pork barbecue was the safest among the street foods analyzed. Knowledge, attitude, and practice scores of respondents were found to be inversely associated with the E. coli load of the three street foods based on Spearman’s rank analysis. The environmental conditions of vending stalls showed moderate to strong association with E. coli load, except for the availability of trash bins, using Cramer’s V. Study results suggest the need to enhance the knowledge on food safety of selected street food vendors and to upgrade their skills in proper purchasing, preparation, handling, and vending of street foods to protect consumer health. Environmental conditions of food vending sites also need to be checked for compliance with sanitation measures and guidelines.